2011
DOI: 10.2528/pierb11052610
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Evaluation of Superstrate Effect on Rectangular Patch Resonator Parameters

Abstract: Abstract-In this paper, modeling and experimentation of a Rectangular Patch Resonator (RPR) covered with a dielectric superstrate are investigated.The RPR criteria are established theoretically and experimentally, to be used in future prospects as an electromagnetic (EM) sensor for the characterization of superstrates. The theoretical model is based on the moment method (MoM) via Galerkin's approach, in which three types of basis and testing functions are used. These functions as well as the spectral dyadic Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
(22 reference statements)
5
9
0
Order By: Relevance
“…So the results indicate that the bandwidth of the rectangular patch microstrip antenna can be increased several times with respect to the isotropic case depending on the adjustment of the anisotropy ratio and patch length. This behavior agrees with that of discovered experimentally for rectangular patches on the isotropic or electric anisotropic substrates [18]. According to the results, it seems to be possible to maintain control of the resonant frequency and obtain wide-band operation using uniaxial substrate having properly selected both permittivity and permeability along the optical and the non-optical axes combined with optimally chosen structural parameters.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…So the results indicate that the bandwidth of the rectangular patch microstrip antenna can be increased several times with respect to the isotropic case depending on the adjustment of the anisotropy ratio and patch length. This behavior agrees with that of discovered experimentally for rectangular patches on the isotropic or electric anisotropic substrates [18]. According to the results, it seems to be possible to maintain control of the resonant frequency and obtain wide-band operation using uniaxial substrate having properly selected both permittivity and permeability along the optical and the non-optical axes combined with optimally chosen structural parameters.…”
Section: Resultssupporting
confidence: 88%
“…To check the accuracy of the spectral domain method described in the previous section for electric anisotropic case, our results are compared with an experimental and theoretical values presented in the previous work [17, 18]. The convergent resonant frequencies for different substrate thicknesses are in an excellent agreement with the experiment results (Table 1).…”
Section: Numerical Results and Discussionsupporting
confidence: 66%
“…From Table 2 it is observed that the bandwidths of a rectangular microstrip antenna computed by the present approach are closer to the experimental [23] and theoretical [24, 25] values. In Table 3, the resonant frequencies obtained by the present approach are compared with the previous results [26, 27]. The comparison shows that the resonant frequencies computed by the present method are in very good agreement with the measured data for a rectangular patch printed on a single substrate.…”
Section: Numerical Results and Discussionsupporting
confidence: 66%
“…The first are concerns the rectangular microstrip patch printed on isotropic substrate, in Table 1 the calculated results of resonant frequencies are compared with recently experimental and theoretical published data [18,19].Also computed results of the resonant frequencies for conducting patch printed on anisotropic substrate are compared with experimental and theoretical values presented in previous work [18,20]. Tables 2 and 3 summarized the measured and computed resonant frequencies for different geometrical antennas.…”
Section: Numerical Results and Discussionmentioning
confidence: 95%